Hepatitis B Virus Double Mutations is There any Role in Pathogenesis of Hepatocellular Carcinoma in Young Patients - Andri Sanityoso Sulaiman; Rino Alvani Gani; Irsan Hasan; Andi Utama; Susan Tai; Griscalia Christine (The Indonesian Society for Digestive Endoscopy, 2009)
Background: The incidence of hepatocellular carcinoma (HCC) below age 40 years old in our institution were relatively high compared with other institutions in Asia. Hepatitis B virus (HBV) basal core promoter (BCP) double mutations correspond with increasing age. The aim of this study was to know if there was any role of HBV double mutations in young HCC patients. Method: A descriptive study was performed on HBV related HCC patients in Cipto Mangunkusumo Hospital in May 2006-November 2008. Patient were recruited consecutively and divided in to two groups, below 40 and above 40 years old. The genotypes were examined by polymerase chain reaction (PCR) method. The alpha feto protein (AFP) values were diagnosed based on ELISA method. The BCP A1762T/G1764A double mutations were examined by direct sequencing. Results: There were 49 HBV related HCC samples consist of 14 (28.5%) samples with age below 40 years old and 35 (71.5%) samples with age above 40 years old. We only found two genotype, genotype B was dominant in patients with HBV related HCC compare to genotype C, 43 (88%) and 6 (12%) respectively. The increasing of AFP level above 400 ng/mL was only found in about half of the samples, 7 (50%) 40 years old, 19 (54%) 40 years old. Double mutations of A1762T/G1764A in BCP occurred in 5 (36%) 40 years old, 15 (43%) 40 years old. Conclusion: The incidence of HBV related HCC in young patients were relatively high. The proportion of patients with AFP level 400 ng/mL in patients below 40 years old were higher compared to patients above 40 years. Keywords: hepatocellular carcinoma, BCP double mutation, HBV genotype